ONLINE ENGLISH SENTENCE CONSTRUCTIONS BY UNDERGRADUATE STUDENTS OF THE ENGLISH EDUCATION DEPARTMENT, NUSA CENDANA UNIVERSITY - Tans Feliks; Hilda M. Nalley; John Bhae (Postgraduate School, Universitas Nusa Cendana, 2021)
This research aimed at finding out: 1. kinds of sentences constructed by semester VI undergraduate students of the English Education Department, School of Teachers Training and Educational Sciences, Nusa Cendana University; 2. their strengths and weaknesses in constructing those sentences; and, 3. solutions to their weaknesses in constructing English sentences. To achieve those aims, this research used descriptive-qualitative research paradigm. The phenomenon to be investigated is how students joining TEFL course constructed certain sentences in communicating with their lecturer or in doing their tasks. The research was done at the English Department of Nusa Cendana University from March 2021 to October, 2021. The instruments used to collect the data were students’online documents and interviews. The data were analysed descriptively based on English grammatical accuracy. It was found that, first, kinds of sentences the students constructed were simple, complex, compound and compound-complex sentences including sentences which are discursive on their own, that is, sentences as complete discourses themselves like “Thank you, Sir!”. Second, the students’ strengths varied: they used various sentence patterns with various words, tenses, structures, and mechanics. Third, their weaknesses were sentence structures, tenses, vocabulary, and mechanics which were not always correctly used. Some sentences, for example, had no subjects or verbs. Fourth, to solve their weaknesses, they say, for example, that they must study harder, memorize English structure, and be more active in reading, writing, speaking and listening in English.